Bronchial thermoplasty: interventional therapy in asthma - Kaukel, Philine; Herth, Felix; Schuhmann, Maren (Therapeutic advances in respiratory disease, 2014)
Bronchial thermoplasty is a new treatment option for patients with severe bronchial asthma who remain symptomatic despite maximal medical therapy. The aim of th...
First published December 10, 2013
Gesehen am 21.10.2020